Barriers and delays in tuberculosis diagnosis and treatment services: does gender matter? - Yang, Wei-Teng; Gounder, Celine R.; Akande, Tokunbo; De Neve, Jan-Walter; McIntire, Katherine N.; Chandrasekhar, Aditya; de Lima Pereira, Alan; Gummadi, Naveen; Samanta, Santanu; Gupta, Amita (Tuberculosis research and treatment, 2014)
Background. Tuberculosis (TB) remains a global public health problem with known gender-related disparities. We reviewed the quantitative evidence for gender-related differences in accessing TB services from symptom onset to treatment initiation. Methods. Following a systematic review process, we: searched 12 electronic databases; included quantitative studies assessing gender differences in accessing TB diagnostic and treatment services; abstracted data; and assessed study validity. We defined barriers and delays at the individual and provider/system levels using a conceptual framework of the TB care continuum and examined gender-related differences. Results. Among 13,448 articles, 137 were included: many assessed individual-level barriers (52%) and delays (42%), 76% surveyed persons presenting for care with diagnosed or suspected TB, 24% surveyed community members, and two-thirds were from African and Asian regions. Many studies reported no gender differences. Among studies reporting disparities, women faced greater barriers (financial: 64% versus 36%; physical: 100% versus 0%; stigma: 85% versus 15%; health literacy: 67% versus 33%; and provider-/system-level: 100% versus 0%) and longer delays (presentation to diagnosis: 45% versus 0%) than men. Conclusions. Many studies found no quantitative gender-related differences in barriers and delays limiting access to TB services. When differences were identified, women experienced greater barriers and longer delays than men.
Gesehen am 17.12.2020